1979
DOI: 10.1007/bf01449756
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of climatic variations and their causal mechanisms

A. Berger

Abstract: Abstract. This paper surveys the history of the Earth's climate and deals with facts, techniques, and causes. A review of climatic history since the origin of the Earth demonstrates the changes and variability of our climate along different scales. These variations can probably be fully understood only when taking into account both external forcing and non-linear interactions between the components of the climatic system: atmosphere, oceans, cryosphere, lithosphere, and biosphere. At least, as far as boundary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…We suggest that timeseries analysis of other long geological records are needed, as well as the traditional geological approach of improving the quality of the narrative. As noted by Berger (1979) the climate spectrum can probably be fully understood only by taking into account both external forcing and nonlinear interactions between the components of the climate system. Recent modeling studies have made advances in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that timeseries analysis of other long geological records are needed, as well as the traditional geological approach of improving the quality of the narrative. As noted by Berger (1979) the climate spectrum can probably be fully understood only by taking into account both external forcing and nonlinear interactions between the components of the climate system. Recent modeling studies have made advances in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…time-series of calculated values of the orbital parameters. Our orbital forcing calculations follow the work of Berger [1977Berger [ , 1978Berger [ , 1979 9-3.4, 3.2-2.9, and 2.7-2.5 my. These intervals would likely be regarded as part of one or more high-stand systems tracts.…”
Section: Statistical Model Based Upon the Last 700000 Yearsmentioning
confidence: 99%
“…; Hays et al (1976) and Briskin and Harrel (1980) found sea-surface temperature estimates and oxygen-isotope fluctuations with dominant periods of about 24, 43, and 105 k.y. The periodicities of the Scycles are similar to those attributed to global climatic changes and are not outside the range of the period of the eccentricity of the Earth's orbit (Milankovitch, 1930;Anderson, 1964;Broecker and Van Donk, 1970;Berger, 1977Berger, , 1979.…”
Section: Causes Of Carbonate Fluctuations At Site 502mentioning
confidence: 68%